Sistem Informasi Kemahasiswaan Fakultas Komunikasi dan Informatika Universitas MUhammadiyah Surakarta - Nugroho, Kukuh Yunantyo; , Nurgiyatna, ST., MSc., PhD (2016)
Student activities are everything activity performed by a student. The Faculty of Communications and Informatic in UMS process data recording related student activities preformed by manual and not use computerized system, therefore it, need for a computerized information system and based website, so the process recording data and data reporting about student activities becomes effective and efficient. These information systems made by using programming language HTML and PHP, for website interface use CSS, and for storage database use MySql .The final result of this system is a website with various features that can solve problems as the submission of proposals, approval proposals, view announcement, registration achievement and scholarship also students data periodic reporting. The system test result of 25 respondents consisting of lecturers, members of ormawa and students, system was going well as required user